Planet Water instead of Planet Earth (2017)
There has been controversy around the name of our planet, in the sense of continuing to call it Earth or better giving it, a name related to water, due to much of our planet is covered by water. Some ecologist trends suggest the second option, whereas scientists consider, it is more pragmatic to leave the name as it is. Throughout the text a recount of the origin of the name of our planet is made, making a tour by the mythology and the religious traditions of some cultures, around the water. Additionally, some of its properties and the importance of this liquid for life in our world are described. Finally, a call for the preservation, care and sustainable use of this resource is made.